Inhibitors and enablers of supply chain integration across multiple supply chain tiers: evidence from Malawi - Kanyoma, K.E.; Agbola, F.W.; Oloruntoba, Richard (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose: This paper investigates the inhibitors and enablers of supply chain integration (SCI) across multiple tiers in the supply chains of manufacturing-based small and medium-sized enterprises (SMEs) in Malawi. Design/methodology/approach: Following a qualitative approach, data were collected through face-to-face interviews across three supply chains, each consisting of a focal manufacturer, a major supplier and a retailer. Findings: The research identified interpersonal relationships, supplier cost transparency and joint supply chain management (SCM) investments as key enablers of SCI. Concerning the inhibitors of SCI, the study found that a lack of external integration inhibited internal integration by acting as a source of disruption to intra-firm processes and relationships. Further, the research found weaker links between manufacturer–-retailer dyads than in manufacturer–supplier dyads, which constrained the ability to achieve multi-tier supplier–manufacture–retailer integration. The study also revealed that resource and infrastructural deficiencies, a culture of fear and intimidation within and between firms, corruption in sourcing transactions and a lack of inter-firm trust inhibited SCI. Research limitations/implications: The paper extends earlier evidence that internal integration is a prerequisite for external integration demonstrating that a basic level of external integration is necessary to prevent disruptions to internal integration. Originality/value: This study is one of the few to go beyond the focal firm perspective and explore the inhibitors and enablers of SCI across multiple supply chain positions, and provides new evidence on the role of external integration in achieving internal integration.